ROLE OF MODERATION OF THE INTERNAL CONTROL SYSTEMS OF THE GOVERNMENT TO STRENGTHEN THE IMPACT OF REGULATIONS ON THE SECURITY OF GOVERNMENT'S WORK AND SERVICES (LKPPS) TO THE ACCOUNTABILITY OF GOODS AND SERVICES (STUDY AT THE PROCUREMENT OFFICE OF BANTEN PROVINCE) - Elnanda Putri, Elen; Zulfikar, Rudi; Mulyadi, Roza (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The aim of this research is to determine the influence of regulations on the accountability of goods and services procurement at the Goods and Services Procurement Bureau in Banten Province and to find out whether the Government's Internal Control System can moderate regulations on the accountability of goods and services procurement at the Goods and Services Procurement Bureau in Banten Province. The analytical method used in this research is a quantitative method. The data collection method used a questionnaire with a total of 60 respondents. Data analysis in this research uses Partial Least Square analysis via SmartPLS 3.0 software. The results of statistical tests show that there is a positive and significant influence of Government Goods and Services Procurement Policy Institution Regulations on accountability, the Government Internal Control System can moderate and significant influence of Government Goods and Services Procurement Policy Institution regulations on accountability.